KONSEP PEMIKIRAN PENDIDIKAN KH HASYIM ASY’ARI DALAM KITAB ADABUL ‘ALIM WAL MUTA’ALLIM - Diana; Saifuddin; Cut Ulfa Miranda (Jurnal Tarbiyah Almuslim, 2023)
The problem of this research is the concept of educational thought according to KH. Hasyim Asy'ari in the book Adabul 'Alim Wal Muta'allim. This study aims to determine the biography and concept of educational thought of KH Hasyim Asy'ari in the book Adabul 'alim Wal Muta'allim. This type of research uses a library approach (library research). The process of collecting data, the author uses a literature survey. In analyzing the data, researchers used content analysis techniques. The research findings inform: first, the virtues of knowledge, 'ulama and learning - teaching. Second, the ethics of students towards themselves. Third, the ethics of students towards educators. Fourth, the etiquette of the learner towards the lesson. Fifth, the etiquette of the educator towards oneself. Sixth, the etiquette of educators in teaching and learning. Seventh, the etiquette of educators towards students. Eighth, manners towards textbooks (kitab).